1985
DOI: 10.1104/pp.78.3.642
|View full text |Cite
|
Sign up to set email alerts
|

Target Molecular Size of the Red Beet Plasma Membrane ATPase

Abstract: Radiation inactivation of the red beet (Beta vulgaris L.) plasma membrane ATPase was carried out using -y-ray radiation from a '37Cs source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…For red beet, radiation inactivation analysis indicates that the target molecular size of the native ATPase is larger than 228 kD and probably exists in the plasma membrane as, at least, a dimer of catalytic subunits (8). Cross-linking studies with the solubilized tomato root plasma membrane ATPase indicate that the enyme could exist as a trimer (2).…”
Section: Discussionmentioning
confidence: 99%
“…For red beet, radiation inactivation analysis indicates that the target molecular size of the native ATPase is larger than 228 kD and probably exists in the plasma membrane as, at least, a dimer of catalytic subunits (8). Cross-linking studies with the solubilized tomato root plasma membrane ATPase indicate that the enyme could exist as a trimer (2).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study from this laboratory (11), radiation inactivation analysis was used to estimate the holoenzyme mol wt of the red beet plasma membrane ATPase when associated with native plasma membrane vesicles. This method involves irradiating protein samples with high energy radiation such as accelerated electrons, x-rays, or '-rays and then analyzing the decrease in enzyme activity with increasing total radiation dose in terms of target theory (4,17 (20).…”
mentioning
confidence: 99%
“…These smaller polypeptides resemble those observed in other plant plasma membrane H+-ATPase preparations (13). The 200-kD phosphopeptide observed in the immunoprecipitates is possibly the dimeric form of the enzyme (6). Because of the presence of <100-kD phosphopeptides in the immunoprecipitates, it is not known if the H+-ATPase is phosphorylated on serine or threonine or both.…”
Section: Discussionmentioning
confidence: 52%
“…Autoradiograms of thinlayer cellulose chromatograms revealed that serine and, to a 5, and 7) or without (lanes 2, 4, and 6) SR and immunoprecipitated with anti-P-1 (lanes 4 and 5), anti-P-2 (lanes 2 and 3), or anti-P-3 (lanes 6 and 7). The immunoprecipitates were hydrolyzed and phosphoamino acids were determined after TLC and autoradiography.…”
Section: Determination Of the Phosphorylated Amino Acidsmentioning
confidence: 97%